Biomarkers responses in different body regions of the polychaeta Hediste diversicolor (Nereidae, Polychaete) exposed to copper - Bouraoui,Z. (2015)
This study aims to evaluate the effects of exposure to 1 µM of copper during a period of test of 48 h, on enzymatic and lipid peroxidation biomarkers in anterior (A), middle (M) and posterior (P) body regions of the polychaeta (Nereididae) Hediste diversicolor. The biomarkers selected in this work were the NADPH cytochrome c reductase (NADPH red) as phase I bio-transformation enzyme, glutathione-S-transferase (GST) as phase II enzyme, and the oxidative stress markers using catalase activity (CAT) and malondialdehyde accumulation (MDA). The NADPH red activity was not significantly affected by copper exposure in the different body regions. Glutathione-S-transferase (GST) was significantly augmented (p< 0.05) only in the A region of Cu group compared to control group. The higher and significant CAT activity (p< 0.05) was noted in the P region of treated group paralleled by a lack of MDA production in the same region. A higher MDA content was observed in A region compared with the same body region of treated worm supporting the idea of a highest oxidant condition in this region.